Declining prevalence of cystic fibrosis since the introduction of newborn screening. Issue 7 (15th June 2010) - Massie, John; Curnow, Lisette; Gaffney, Lydia; Carlin, John; Francis, Ivan
Abstract : Objectives: Newborn screening for cystic fibrosis (CF) facilitates early diagnosis and genetic counselling for parents of affected infants. Many parents elect to use prenatal testing for subsequent pregnancies, and this may affect the prevalence of CF. The aim of this study was to assess the evidence for changes in the live-birth prevalence of CF since the introduction of newborn screening for CF. Methods: The authors reviewed the records of the Victorian newborn screening programme and the clinical records of the three centres caring for patients with CF in Victoria, Australia, in order to determine the live-birth prevalence of patients with CF; before (1979–1988) and after (1989–2006) the introduction of newborn screening. The authors reviewed the records of the Victorian Clinical Genetics Service to ascertain the number and outcome of prenatal tests for CF (1979–2006). Live births in Victoria were obtained from the state birth register. Findings: Between 1979 and 1988, the live-birth prevalence of CF was 3.96 (95% CI 3.48 to 4.49) per 10 000 live births. Following the introduction of newborn screening (1989–2006) the live-birth prevalence of CF was 3.28 (95% CI 2.97 to 3.63) per 10 000 live births, representing a reduction of 17% (95% CI 2% to 29%, p=0.025). In the prescreening period, there were 10 prenatal tests, which identified three affected pregnancies, all of which were terminated. In the later period, there were 304 prenatal tests (mean 17/year), of which 76 were affected, and 70 of these pregnancies were terminated. Conclusion: The authors observed a modest reduction in the live-birth prevalence of CF since the introduction of newborn screening. This is principally due to at-risk couples detected by newborn screening electing to use prenatal testing on subsequent pregnancies.